The Effect of Phase I of Cardiac Rehabilitation on Length of Stay for Coronary Heart Disease Patients at Mardi Waluyo Hospital, Blitar City - Cholis, Eko Prastyo; Nurachmah, Elly; Adam, Muhamad (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
Coronary Heart Disease (CHD) is a specific term for a cardiovascular disease characterized by narrowing coronary artery tissue mainly due to atherosclerosis that causes microangiopathy. CHD patients in the treatment, in addition to receiving treatment, also receive rehabilitation to help speed up the recovery from physical, psychological, and social conditions. The rehabilitation program should be given since admission to the hospital, known as phase I of Cardiac Rehabilitation. One of the components of phase I of Cardiac Rehabilitation is a physical activity aimed at speeding up the recovery of the patient's condition to return to regular activities. This study aims to determine the relationship between cardiac phase I rehabilitation for the length of patient care for CHD in Mardi Waluyo Hospital Blitar City. This study used a quasi-experimental design with the post-test only non-equivalent group. The sample in this study consisted of 14 respondents from the intervention group and 14 patients for the control group respondents who were diagnosed with CHD in Mardi Waluyo Hospital, Blitar City, matching the specified inclusion criteria. The results showed a significant correlation between heart phase I rehabilitation on the duration of care (p-value = 0.007). The statistical test used a bivariate correlation test with the Mann-Whitney Test. This result yielded that it needs to be given early on to CHD patients as it can help the healing process and shorten hospitalization. Furthermore, the shorter length of care will further save the operational costs of CHD patient care.